Everyday Encounters in Public Transport: Mapping Bus Behaviour in Maribor - Huszti, Márton; Evtimov, Boris; Bajda, Kornelia; Nagy, Zsombor; Němec, Filip; Maroš Monsberger, Martin; Kolar, Tilen (Quality of Life in a Changing World: Spatial, Social and Environmental Perspectives from Maribor and Beyond, 2026)
This paper examines the emotional and social expressions of the local transportation passengers in the city of Maribor. While transport research typically emphasises technical efficiency, this study examines the lived and emotional aspects of mobility. Through systematic observation of four bus routes, we documented behaviours, interactions, and spatial contexts across weekday and weekend journeys. The findings show that public transport in Maribor is primarily used by students, the elderly, and those without cars, reflecting the country’s high motorisation rate and the social stigma associated with bus travel. Passenger moods were frequently marked by fatigue and disengagement, often expressed through phone use or passive waiting. Yet moments of social connection, such as casual conversations or small acts of kindness, revealed that buses can also provide comfort and a sense of community. These insights highlight how public transport functions not only as a technical system but also as an emotionally and socially meaningful space.